60. Dysphagia in different types of myopathy. Issue 1 (January 2015) - Bongiovanni, L.G.; Rossini, F.; Bonato, G.; Barbieri, F.; Tonin, P.; Vattemi, G.; Franchini, E.; Demrozi, A.; Benini, L.
<x xml:space="preserve">Abstract</x> Oculopharyngeal Muscular Dystrophy (OPMD) is a myopathy characterize by ptosis and marked swallowing impairment. Dysphagia may also occur in some mitochondrial diseases. Previous reports focused on the proximal (skeletal) parts of oesophagus only. We tried to analyse proximal and distal oesophageal function and the role of parasympathetic system and myenteric plexus in such disorders. Four male dysphagic patients, 3 affected by sporadic OPMD and 1 with single mitochondrial DNA deletion and "OMPD- like" phenotype, were studied. Both adrenergic and cholinergic functions of autonomic system were investigated. High resolution manometry with 22 perfused channels was used to assess the oesophageal function. Beside the involvement of the proximal portion of the oesophagus (striated muscle), smooth muscles seemed also to be affected in OPMD patients; normal peristaltic waves were found in only about 50% of swallows. In the patient with mitochondrial DNA deletion absent peristalsis involving both striated and smooth muscle in 100% of swallows was observed. Since autonomic tests were normal in all patients, progressive reduction of peristalsis in the oesophageal distal part could be related to myenteric plexus derangement or to smooth cell muscle disease.